2015
DOI: 10.1007/s00264-015-3072-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and a prognostic model of hip periprosthetic infection recurrence after surgical treatment using articulating and non-articulating spacers

Abstract: Efficacy of the first step of two-stage revision was 64.1 %. Placement of either articulating or non-articulating spacers did not influence recovery from PJI. Laboratory values of ESR, CRP, BMI and the type of previous surgery were identified as main factors that affect outcomes of the two-stage procedure. A prognostic model with the calculation of a total risk score for PJI recurrence was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
1
18
0
1
Order By: Relevance
“…Tikhilov et al used total risk score to calculate the risk of infection recurrence after two-stage procedure. They found BMI was identified as one of main factors related to infection recurrence [13]. Our study agreed with Tikhilov et al We used multivariate analysis and found BMI≥30 kg/m 2 was associated with an increased risk for treatment failure following two-stage reimplantation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Tikhilov et al used total risk score to calculate the risk of infection recurrence after two-stage procedure. They found BMI was identified as one of main factors related to infection recurrence [13]. Our study agreed with Tikhilov et al We used multivariate analysis and found BMI≥30 kg/m 2 was associated with an increased risk for treatment failure following two-stage reimplantation.…”
Section: Discussionsupporting
confidence: 88%
“…However, few studies have been done to analyze the risk factors of failed reimplantation protocol [6, 13]. The purpose of this study was to investigate the patient-related risk factors associated with treatment failure following the reimplantation protocol in hip PJI.…”
Section: Introductionmentioning
confidence: 99%
“…Despite all sterilization conditions and antibiotic prophylaxis, PIJ is seen, even though rarely, and it continues to be the most fearful nightmare of orthopedic surgeons (Zmistowski et al ., ; Tikhilov et al ., ; Yoon et al ., ). Debridement and breaking are performed if PJI occurs in the early period; however, if it is seen late, all the implants are removed and concurrent or two‐stage revision surgery is performed (Tikhilov et al ., ; Yoon et al ., ). However, despite all these treatments, reinfection rates may become 25% after revision surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…The most common gram‐negative bacteria are Pseudomonas aeruginosa and Acinetobacter . PJI recurrences caused by these bacteria are higher than those caused by gram‐positive bacteria (Tikhilov et al ., ). The reason for this is that the active microorganism is unknown and the biofilm layer, which is a formed cause the bacteria to become resistant to treatment.…”
Section: Introductionmentioning
confidence: 97%
“…[3]. Особое место в структуре осложнений занимают инфекционные осложнения [4,5]. doi: 10.21823/2311-2905-2019-25-4-141-149 Early Deep Periprosthetic Hip Infection of Odontogenic Origin (Case Report) T.u Deep periprosthetic joint infection (PJI) is a severe complication after primary and revision hip joint arthroplasty resulting in multiple interventions on the joint.…”
Section: Introductionmentioning
confidence: 99%